Adsorption and Desorption Metal Cu (II) using Zeolite Synthetic by Bottom Ash Coal Modified Dithizone - Yuan Sidarta; Didik Krisdiyanto; Khamidinal Khamidinal (Kaunia: Integration and Interconnection Islam and Science Journal, 2022)
Zeolite synthetic and zeolite modified dithizone has been succesfully created by hydrotermal method. The aim of this research is to know the characteristics of zeolite synthetic and zeolite modified dithizone and to know capacity of adsorption and desorption. The effect of various variables, such as pH, concentration of Cu (II), contact time and temperature was investigated using batch process,  characterization zeolite modified dithizone and zeolite synthetic using XRD,  XRF, FTIR and GSA. The result of characterization bottom ash coal by hydrotermal reaction using XRF, be discovered composition Si as many 82,01% and Al 8,54%. product of melting hydrothermally indicate a specific zeolite IR absorption at a wavelength of 300-1250 cm-1. The result XRD showed that be found zeolite-X, zeolite-A, zeolite sodalite and difatogram of dithizone. Zeolite modified dithizone has been succesfully synthesized with a marked presence group of –NH and –SH by using FTIR. Zeolite modified dithizone surface area change from 160,262 m2/g to 69,609 m2/g. The best adsorption metal Cu(II) by zeolite synthetic is pH 7. Kinetics adsorption zeolite synthetic and zeolite modified dithizone follow kinetics of pseudo second orde, with R2 respectively 0,7378 and 0,8689, rate constant of pseudo second orde adsorption at zeolite synthetic  is -0,017 g/mg.min-1 and zeolite modified dithizone -0,013 g/mg.min-1. Isotherm type for both of adsorbent follow Langmuir isotherm. Desorption of metal Cu(II) on zeolite modified dithizone and zeolite synthetic a lot off obtained using HCl at level 47,08% and 41,49% respectively.